Control of helical chirality in supramolecular chromophore–DNA architectures. Issue 9 (14th January 2019) - Hofsäβ, Robert; Ensslen, Philipp; Wagenknecht, Hans-Achim
Abstract : Four differentd - andl -configured chromophore–2′-deoxyuridine conjugates were applied to elucidate the helical chirality of their non-covalent assemblies along thed - andl -configured DNA templates by optical spectroscopy. Abstract : Four differentd - andl -configured chromophore–2′-deoxyuridine conjugates were applied to elucidate the helical chirality of their non-covalent assemblies along thed - andl -configured DNA templates by optical spectroscopy. There is no configuration-selective recognition between these nucleosides and the DNA templates. The helicity of the DNA assemblies is either controlled by the configuration of the DNA template or by the nucleoside configuration.